Quasi Z source five phase inverter delivering two independent three phase loads - Raghuram M.; Kumar A.; Singh S.K. (My University, 2025)
This paper proposes a new topology which produces two three phase outputs operating at different fundamental frequencies outputs with buck boost capability. The proposed topology is derived based on the concept of impedance source network and five phase inverter. To achieve this, switching strategy based on space vector modulation analysis is developed to carefully insert the shoot through period in a switching cycle with out disturbing the conventional inverter operation. In addition, steady state analysis is presented. MATLAB simulation is preformed on proposed converter to show the effectiveness of the converter. © 2022 IEEE.